Mungbean: A New Alternative Crop for Kansas Farmers - Natalia da Silva Volpato; Claire Bott; Victor Gimenez; Ana Julia Paula Carcedo; Ignacio A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2024)
Over the last two decades, mungbean demand has significantly increased worldwide and in the United States (US), driving production increases. This crop is primarily used for human consumption due to its high content of protein. However, the factors causing yield variability are not widely known. Therefore, the objective of this study is to determine the critical period for seed yield in mungbean crops. A field experiment was conducted using shading treatments at different periods throughout the crop cycle to investigate the effects of plant stress at different stages. The critical period for seed yield determination seems to be concentrated during the R1 through R4 growth stages (flowering until the end of grain filling). Changes in the number of seeds per unit area and seed weight were correlated with the crop growth rate during the critical period for yield determination.
Keywords: Vigna radiata (L. Wilczek); crop diversification; seed yield; critical period; protein rich crop